An Update on Molecular Diagnostics for COVID-19 - Islam, Khursheed Ul; Iqbal, Jawed (Frontiers in Cellular and Infection Microbiology, 2020)
A novel strain of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) disease (COVID-19) has been recently identified as an infectious disease affecting respiratory system of humans. This disease is caused by SARS-CoV2 that was identified in Chinese patients having severe pneumonia and flu like symptoms. COVID-19 is a contagious disease that spreads rapidly via droplet particles arising via sneezing and coughing action of an infected person. The reports of asymptomatic carriers changed the scenario of symptom based diagnosis in COVID-19 which intensified the urge of proper diagnosis of maximum of the population to combat the rapid transmission of virus. Diagnosis of positive cases is necessary to ensure prompt care to the affected people and also to curb further spread of infection in the population. Collecting samples at the right time, from the exact anatomical site is crucial for proper molecular diagnosis. After the complete genome sequence got available, China formulated RT-PCR as a primary diagnostic procedure for detecting SARS-CoV2. Many in-house and commercial diagnostic kits have also been developed or are under development that detects SARS-CoV2 infection. Serological based diagnosis is another broad category of testing that can detect different serum antibodies like IgG, IgM and IgA in an infected patient. PCR based diagnostic procedures that are commonly used for pathogen detection needs sophisticated machines and assistance of a technical expert, despite their reliable accuracy, they are not cost effective tests where a common man can afford, so it becomes imperative to look for other diagnostic approaches which could be cost effective, rapid, and sensitive with consistent accuracy. To make such diagnosis available to common man, many techniques can be exploited among which Point of Care (POC) also known as bed side testing which is developing as a portable and promising tool in pathogen diagnosis. Other LFA based techniques like SHERLOCK, CRISPR-Cas12a (AIOD-CRISPR) etc. have shown promising results in rapid detection of pathogens. This review highlights the importance of nucleic acid based diagnostic techniques and other protein based and point of care testing strategies in diagnosing SARS-CoV2 infection during the current pandemic.